The Excavations at Nimrud (Kalḫu), 1952 - Mallowan, M. E. L.
Areas Investigated — Excavations in the "Burnt Palace" — Stratification — Chronology of the Palace — Excavations in the NW-Palace of Aššur- naṣir-pal II. The Well in Room NN. — Excavations in the N-Wing of the NW-Palace — Excavations in the Courtyard outside Gate D — The Ancient River Wall and Quay of Calah.